WeChat-based health education to improve health knowledge in three major infectious diseases among residents: a multicentre case-controlled protocol - Yan Qiu; Jingjing Ren; Kaijin Xu; Hongli Qin; Meike Ying (BMJ Open)
Introduction Health literacy (HL) in infectious diseases is inadequate in China. Since the first nationwide survey of HL conducted in China, great efforts have been made. However, the rate of HL in infectious diseases was 16.06% in 2017. In contrast, with an HL rate of 15.85% in 2008, no significant effect was observed over 10 years. With an increasing number of internet users, we aim to assess the effects of WeChat-based health education for the promotion of partial HL-health knowledge in infectious diseases.Methods and analysis A total of 2160 residents aged 15–69 years old will be enrolled in this study. The primary outcome measures will be the rate of health knowledge in infectious disease. The follow-up period is 3 years.Ethics and dissemination The study protocol was approved by the Research Ethics Committee of the First Affiliated Hospital, College of Medicine, Zhejiang University. The findings of this study will be submitted to a peer-reviewed journal.